1991
DOI: 10.1128/jvi.65.5.2695-2698.1991
|View full text |Cite
|
Sign up to set email alerts
|

Unintegrated human immunodeficiency virus type 1 DNA in chronically infected cell lines is not correlated with surface CD4 expression

Abstract: Using a polymerase chain reaction-based assay on total cell Ijsates, we have detected unintegrated human immunodeficiency virus type 1 (HIV-1) DNA in chronically infected T-lymphocytic (ACH-2, J1) and promyelocytic (OM-10.1) cell lines. Treatment with 3'-azido-3'-deoxythymidine (AZT) or soluble CD4 inhibited accumulation of unintegrated viral DNA about 10-fold within 72 h; removal of AZT permitted recovery to pretreatment levels within 72 h. Our results indicate that unintegrated HIV-1 DNA is unstable in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The same studies also demonstrate that defective viruses negatively affect or abolish reinfection events in a manner similar to that of AZT. This finding is in accord with a previous work which demonstrated that in OM-10.1 cells, AZT led to a reduction in integrated viral DNA probably by a mechanism of inhibition of reinfection events (6). We further investigated the basis for the inhibitory effect mediated by defective particles and determined that neither modulation of CD4 nor changes in cellular proliferation are responsible for the observed phenomenon.…”
Section: Discussionsupporting
confidence: 91%
“…The same studies also demonstrate that defective viruses negatively affect or abolish reinfection events in a manner similar to that of AZT. This finding is in accord with a previous work which demonstrated that in OM-10.1 cells, AZT led to a reduction in integrated viral DNA probably by a mechanism of inhibition of reinfection events (6). We further investigated the basis for the inhibitory effect mediated by defective particles and determined that neither modulation of CD4 nor changes in cellular proliferation are responsible for the observed phenomenon.…”
Section: Discussionsupporting
confidence: 91%
“…Because OM-10.1 cells remain CD4+ until viral activation, the possibility exists for superinfection of nonproducing cells by virions released from the small percentage of cells constitutively expressing HIV-1. An acute superinfection of OM-10.1 cells is responsible for an accumulation of extrachromosomal HIV-1 DNA (1), as demonstrated in other HIV-1-infected cell systems (1,32,33,37). Azidothymidine treatment of OM-10.1 cultures prevents the accumulation of unintegrated HIV-1 DNA (1) without affecting the activation of the integrated HIV-1 provirus by TNF-a (2,34).…”
Section: Discussionmentioning
confidence: 99%
“…PBL were isolated and stimulated with PHA-IL2, and MDM were cultured for 3 days prior to infection with DNase treated HTLV-IIIB. MDM (1) were infected at an MOI of 3, and MDM (2) were infected at an MOI of 1. Cells were harvested at the indicated time points and subjected to PCR under standard conditions (9) using primers noted in the text.…”
Section: Rnu N Hiv-l Gag (118 Bp)mentioning
confidence: 99%